(untitled) - George A Wistreich (New Jersey, 1997)
The book begins with a short visual survey of equipment generally used in a microbiology laboratory. It teaches certain fondamental procedures used in microscopy and in study of microorganisms, methods employed in the isolation and study of both aerobic and anearobic microbial cultures; compares the representative microbial groups, which include bacteria, algae, protozoa, and fungi, as to their structure, morphological arrangement, and selected activities; demonstrates specific staining techniques, such as the Gram Stain and acid-fast procedures, the structure and function of bacterial cells, including techniques used to observeflagella and bacterial motility by means of motility agar, the extracellular and intracellular metabolic activities of bacteria, the principles of sterilization and disinfection, and the effectiveness of chemical and physical agents in the control of microorganisms; emphasizes certain properties of viruses, including exercises involving gene transfer processes found in bacteria; demonstrates some of the industrial applications of microorganisms, including exercises covering the distribution of microbes in food and their involvement in the production of sauerkraut, cheese, yogurt, and wine. It also presents the process of phagocytosis and an enzyme immunoassay; provides a number of exercises dealing with epidemiology, exercises relating to several aspects of basic medical microbiology; provides an introduction to the fundamental areas of medical helminthology. Finally, the book presents the exercises that include topics such as determining the effects of temperature on the bacterial growth curve, immunoelectrophoresis, the polymerase chain reaction (PCR), and DNA restriction analyses
Keywords: microbiology - experiments